(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we have studied special class of bipartite graphs associated with 3 uniform semigraphs of path graph \( P_m,1 \) and star graph \( S_m,1 \) and estimated some topological indices such as Wiener index, Detour index, Circular index, Cut Circular index, vertex PI index and vertex Co-PI index of these graphs.